Comprehending and Speaking about Motion in L2 Spanish : A Case of Implicit Learning in Anglophones - Navarro Ortega, Samuel A. (Springer International Publishing : Imprint: Palgrave Macmillan, 2017)
This book presents a novel analysis of the learning of motion event descriptions by Anglophone students of Spanish. The author examines cross-linguistic differences between English and Spanish, focusing on the verbal patterns of motion events, to explore how learners overcome an entrenched first-language preference to move toward the lexicalization pattern of the additional language. His findings highlight the gradual nonlinear process Anglophones traverse to acquire and produce form-meaning mappings describing motion in Spanish. The author suggests that as motion event descriptions are not normally the focus of explicit instruction, students learn this concept primarily from exposure to Spanish. Given its interdisciplinary nature, this book will be of interest to researchers working in Hispanic linguistics, cognitive semantics, and Spanish language learning and teaching.
Keywords: Linguistics.; Applied linguistics.; Psycholinguistics.; Romance languages.; Semantics.; Lexicology.; Language and education.; elektronické knihy; electronic books